2015
DOI: 10.1007/s11249-015-0488-3
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation Bubble Measurement in Tribological Contacts Using Digital Holographic Microscopy

Abstract: The use of advanced measurement techniques such as the digital holography method described in this paper improves the understanding of the cavitation phenomenon in tribological contacts such as the sliding contact of the piston ring-cylinder liner conjunction. The paper describes the use of digital holography measurement technique to measure cavitation bubble formation and thickness. The position of observed lubricant film rupture preceding the cavitation region is compared with some commonly predicted boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Arcoumanis et al [49,50] have also documented the cavitation pattern variation in reciprocating piston ring-liner assemblies while simultaneously measuring the lubricant film thickness, either by employing capacitance [49] or laser induced fluorescence [50]. Most recently, Tang et al [51] employed a digital holographic microscope to perform measurements of the cavitation bubbles generated in a sliding linear contact replicating the ring-liner pair. They observed closed cavitation streamers when a plane glass was driven by a bi-directional translation stage against a cylindrical lens.…”
Section: Cavitationmentioning
confidence: 99%
“…Arcoumanis et al [49,50] have also documented the cavitation pattern variation in reciprocating piston ring-liner assemblies while simultaneously measuring the lubricant film thickness, either by employing capacitance [49] or laser induced fluorescence [50]. Most recently, Tang et al [51] employed a digital holographic microscope to perform measurements of the cavitation bubbles generated in a sliding linear contact replicating the ring-liner pair. They observed closed cavitation streamers when a plane glass was driven by a bi-directional translation stage against a cylindrical lens.…”
Section: Cavitationmentioning
confidence: 99%
“…Most recently, [16] reported the measurement of the oil film thickness for different lubricant using LIF and showed that the formulation and chemistry of the lubricant play a major role in the oil film thickness curves and that the cavitation structure is affected by speed and load. Another useful technique to visualise and measure cavitation bubble formation and its thickness is the digital holography method, which was described by [17] and used for the first time in an optical sliding bearing system. They showed that it is possible to produce high-resolution images to measure the bubble thickness and position.…”
Section: Introductionmentioning
confidence: 99%
“…The viscosity of the oil, sliding speed, and film shape are the same with the values in the experiments, while the film thickness measured by the optical interferometry is used as h min . 6 1 1 6 1 1…”
Section: Simple Numerical Analysis For Initial Stage Of Cavity Growthmentioning
confidence: 99%
“…The phenomena related to cavitation include cavitation erosion, starvation, and breakdown of lubrication film in bearings, which are negative effects, but also reducing the friction coefficient and improving seal performance in seals and bearings, which are positive effects. Recently, the cavitation phenomena in the machine elements, such as journal bearing [2,3], seal [4], piston ring-cylinder liner [5,6], microtextured surface [7,8], have been studied by experimental observation and numerical simulation.…”
Section: Introductionmentioning
confidence: 99%